2021
DOI: 10.1111/1755-0998.13353
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome‐level reference genome of the soursop (Annonamuricata): A new resource for Magnoliid research and tropical pomology

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 70 publications
3
18
0
Order By: Relevance
“…For the second genomic DNA sequencing approach, the sequencing library was prepared using the SMRTbell Express Template The third genomic DNA sequencing approach was the generation of a Hi-C library, as recently described (Strijk et al, 2021). Briefly, the steps were as follows: (1) DNA cross-linking, (2) MboI digestion,…”
Section: Dna Sequencing and Quality Controlmentioning
confidence: 99%
“…For the second genomic DNA sequencing approach, the sequencing library was prepared using the SMRTbell Express Template The third genomic DNA sequencing approach was the generation of a Hi-C library, as recently described (Strijk et al, 2021). Briefly, the steps were as follows: (1) DNA cross-linking, (2) MboI digestion,…”
Section: Dna Sequencing and Quality Controlmentioning
confidence: 99%
“…The assembly statistics of this study showed a higher number of assembled transcripts and unigenes compared to other Annonaceae transcriptomes [ 19 , 20 , 21 ]. Recently, the first soursop genome was assembled at a chromosome level from PacBio and Illumina short-reads, identifying 23,375 protein-coding genes using de novo RNA-seq and homology searches [ 22 ]. In this study, similar results were obtained, finding 21,494 ORF from 95,832 unigenes under different postharvest storage conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of new sequencing technologies is certainly evident, it has not been possible to assemble a gap-free genome from telomere to telomere only by shortread sequencing. In more recent genome sequencing projects with high-quality published genomes [36][37][38][39][40][41], the scaffolding of long-read assemblies was complemented with high-throughput long-range data, such as optical maps (BioNano Genomics, San Diego, CA, USA [42,43]), chromosomal conformation sequencing (Hi-C with in vivo fixation of chromosomes [44,45]), or linked-reads sequencing (10× Genomics, 10× Genomics, Inc., Pleasanton, US [46]). Long-range mapping data and long-read sequencing allow haplotype/subgenome-phasing of several tree genomes [47][48][49], solving, to a certain extent, challenges in the complete assembly of highly heterozygous and complex genomes.…”
Section: Approaches For Sequencing Of the Large And Heterozygous Tree...mentioning
confidence: 99%